Activation of TRPV4 by mechanical, osmotic or pharmaceutical stimulation is anti-inflammatory blocking IL-1β mediated articular cartilage matrix destruction. Issue 1 (January 2021) - Fu, S.; Meng, H.; Inamdar, S.; Das, B.; Gupta, H.; Wang, W.; Thompson, C.L.; Knight, M.M.
Summary: Objective: Cartilage health is maintained in response to a range of mechanical stimuli including compressive, shear and tensile strains and associated alterations in osmolality. The osmotic-sensitive ion channel Transient Receptor Potential Vanilloid 4 (TRPV4) is required for mechanotransduction. Mechanical stimuli inhibit interleukin-1β (IL-1β) mediated inflammatory signalling, however the mechanism is unclear. This study aims to clarify the role of TRPV4 in this response. Design: TRPV4 activity was modulated glycogen synthase kinase (GSK205 antagonist or GSK1016790 A (GSK101) agonist) in articular chondrocytes and cartilage explants in the presence or absence of IL-1β, mechanical (10% cyclic tensile strain (CTS), 0.33 Hz, 24hrs) or osmotic loading (200mOsm, 24hrs). Nitric oxide (NO), prostaglandin E2 (PGE2 ) and sulphated glycosaminoglycan (sGAG) release and cartilage biomechanics were analysed. Alterations in post-translational tubulin modifications and primary cilia length regulation were examined. Results: In isolated chondrocytes, mechanical loading inhibited IL-1β mediated NO and PGE2 release. This response was inhibited by GSK205. Similarly, osmotic loading was anti-inflammatory in cells and explants, this response was abrogated by TRPV4 inhibition. In explants, GSK101 inhibited IL-1β mediated NO release and prevented cartilage degradation and loss of mechanical properties. Upon activation, TRPV4 cilia localisation was increased resulting in histone deacetylase 6 (HDAC6)-dependent modulation of soluble tubulin and altered cilia length regulation. Conclusion: Mechanical, osmotic or pharmaceutical activation of TRPV4 regulates HDAC6-dependent modulation of ciliary tubulin and is anti-inflammatory. This study reveals for the first time, the potential of TRPV4 manipulation as a novel therapeutic mechanism to supress pro-inflammatory signalling and cartilage degradation.